Prescribing drugs in Renal Failure: A Judicious Approach - Dutta, Pradip Kumar (Bangladesh Journal of Medicine, 2023)
Prescribing drugs in renal failure is essential to reduce their toxic effects due to unusual accumulation in renal failure. It is because of less protein binding and prolong half life of elimination in case of renal failure. Usually the toxicity of the drug is reduced by either diagnosing serum level of the specific drug or by measuring eGFR of the particular patient. We commonly use three methods in these cases to reduce the side effect of the drugs 1. Interval extension, 2. Dose reduction. 3. Combination of the above two. In case of patients on hemodialysis the drugs which are not protein bound are easily eliminated, so in such cases the drugs are either given after hemodialysis or giving a fraction of the individual dose just after hemodialysis. In case of Renal Transplantation prescribing drugs requires knowledge of the drug-drug interection. It is to be remembered that to get the immediate therapeutic efficacy of the drug in case of renal failure the loading dose is same as that of patients without renal failure, only the maintenance dose is either reduced or given with a prolong interval or both. The following drugs are specially important during prescribing in Renal Failure 1. NSAIDS 2. Psyhotherapeutic drugs 3. Antimicrobials and 4. Cardiovascular Drugs. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 180